English Comic Web-Toon and Reading Motivation Toward Student's Reading Comprehension: English - Nasrullah; Tahrun; Mulyadi (Journal of English Development, 2024)
This research aims to get empirical evidence using English Comic Web-Toon and reading motivation on Reading Comprehension. The sample of this study numbered 60 students, 30 students for experimental classes and 30 for the control class, who were selected using sampling techniques. Before researchers gave treatment, students from the two classes were given a preliminary test to discover their ability to read the narrative text. Then, they were given a final test after treatment to see the progress. This research instrument has 25 multiple-choice questions. The methods used in this research are Quantitative and employ Factorial designs. In analyzing the data, examiners use t-tests. The calculation shows a t-table value significance. It suggests that to be higher than the t-table, the average value levels of the experiment class are higher than the value of the control class. Additionally, English Comic Web-Toon and reading motivation are highly effective in reading comprehension to read English texts of the eleventh SMA N 1 Lempuing academic year 2023/2024.